Comparative Study on Wear Characteristics between Flow Mode and Shear Mode Magnetorheological Dampers. Issue 3 (4th May 2018) - Kim, Wan Ho; Park, Jhin Ha; Park, Jinhyuk; Kim, Gi-Woo; Lee, Yang-Sup; Choi, Seung-Bok
ABSTRACT: This comparative study experimentally examines the wear characteristics of magnetorheological (MR) dampers operated in flow mode and shear mode. First, electromagnetic coil structures are designed for two different MR dampers to maximize the field-dependent damping force. Two MR dampers are also designed to have the same volume of MR fluid for reasonable comparison. After identifying the field-dependent damping force at the initial state, the two dampers are operated up to 60, 000 cycles using a reciprocating-type wear durability tester. The field-dependent damping forces are then evaluated before and after operation. The wear properties of the MR fluid are investigated using scanning electron microscope (SEM) images that show the changes in the MR fluid particles' size and shape. The surface roughness of the MR damper's piston areas are also measured. In addition, the effects of the permeability of the piston sleeve materials on the wear properties are investigated by selecting three different sleeve materials that have different permeability values: 0.2% carbon steel (S20C), 0.45% carbon steel (S45C), and tool die casting steel (STD-11). The surface roughness of each case is tested and the atomic spectrum is investigated after long operation using energy-dispersive X-ray spectroscopy (EDS) inside the piston. The experimental results obtained from this work indicate that the motion of the operating mode significantly affects the wear characteristics of the MR fluid itself as well as the magnetic effective areas of the MR dampers.